2002
DOI: 10.1002/ijc.10313
|View full text |Cite
|
Sign up to set email alerts
|

Circulating enterolactone and prostate cancer risk: A Nordic nested case‐control study

Abstract: Enterolactone, a phytoestrogen belonging to the class of lignans, is produced by the intestinal microflora from precursors in plant foods and has been implicated in protection against cancer. We study the effect of enterolactone on the risk of a subsequent diagnosis of prostate cancer. We con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 31 publications
8
51
2
Order By: Relevance
“…One case -control study found a 60% reduction in prostate cancer risk associated with a high concentration of serum enterolactone (Heald et al, 2007), but no relationship was seen in other studies that measured enterolactone in serum, plasma, or urine (Stattin et al, 2002(Stattin et al, , 2004Kilkkinen et al, 2003;Low et al, 2006;Hedelin et al, 2006b). One possible reason for the lack of associations in earlier studies is that enterolactone levels were too low for a protective effect to be observed (Heald et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…One case -control study found a 60% reduction in prostate cancer risk associated with a high concentration of serum enterolactone (Heald et al, 2007), but no relationship was seen in other studies that measured enterolactone in serum, plasma, or urine (Stattin et al, 2002(Stattin et al, , 2004Kilkkinen et al, 2003;Low et al, 2006;Hedelin et al, 2006b). One possible reason for the lack of associations in earlier studies is that enterolactone levels were too low for a protective effect to be observed (Heald et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…While data on enterolactone from the α‐Tocopherol, β‐Carotene Cancer Prevention Study (214 case patients)25 and the Helsinki Heart Study (136 case patients)18 were not available for this analysis, their results do not differ materially from those reported here, and it is unlikely that these data would have changed our summary risk estimates. The Multiethnic Cohort (MEC) study,27 in which phytoestrogen concentrations were measured in urine, found a weak inverse association between genistein and daidzein concentrations and prostate cancer risk, which did not differ across the four ethnic groups examined (African Americans, Japanese Americans, Latinos, Whites).…”
Section: Discussionmentioning
confidence: 69%
“…Individual participant data were available from seven nested case–control studies by the date of dataset closure (November 2017): the European Prospective Investigation into Cancer and Nutrition (EPIC) (cases diagnosed from June 1999 to January 2003 (designated Phase 1);15 cases diagnosed from February 2003 to December 2006 (designated Phase 2),16 EPIC‐Norfolk17 (for participants not included in either the EPIC Phase 1 or Phase 2), Janus Nordic Biological Specimen Biobank Working Group (NBSBWG),18, 19, 20 Japan Collaborative Cohort Study (JACC),21 Japan Public Health Center‐based prospective Study (JPHC),22 the Malmö Diet and Cancer Study (MDCS)23 and the Northern Sweden Health and Disease Cohort (NSHDC) 24. Three of these studies contributed data on genistein (1,846 cases, 2,200 controls), four had data on daidzein (1,239 cases, 1,675 controls) and equol (1,209 cases, 1,571 controls), five had data on enterolactone (2,828 cases, 5,593 controls) and two studies had data on enterodiol (1,002 cases, 1,197 controls).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations